Synthesis and properties of fluorescence poly(benzoxazole–imide)s containing naphthalene. (September 2015) - Ma, X.; Ma, X.; Qiu, X.; Jin, R.; Kang, C.; Gao, L.
Novel aromatic poly(benzoxazole–imide)s containing naphthalene were prepared from synthesized 1, 4-di(5-aminobenzoxazol-2-yl)naphthalene and commercial dianhydrides by conventional two-step polymerization. The polymers showed high levels of tensile strength of up to 294 MPa and modulus of up to 6.5 GPa. The glass transition temperatures of the polymers were observed between 267°C and 345°C. The 5% weight loss temperatures of the polymers were tested in the range of 517–562°C in nitrogen atmosphere. The excellent properties of polymers were attributed to their rigid-rod-like molecular structure. The polymers emitted different fluorescence with maximum emission wavelengths in the range of 470–560 nm. Increasing the dianhydride electron affinity, the emission spectra peak value of polyimides (PIs) except PI6 increased gradually, but the fluorescent intensity of the PIs decreased. The 1, 4-bis(3, 4-dicarboxyphenoxy)benzene dianhydride-derived PI film exhibit highly fluorescent characteristics; however, the PI film from pyromellitic dianhydride was nonfluorescent.